2016
DOI: 10.1016/j.ejrad.2016.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Heart deformation analysis for automated quantification of cardiac function and regional myocardial motion patterns: A proof of concept study in patients with cardiomyopathy and healthy subjects

Abstract: Objective To test the performance of HDA in characterizing left ventricular (LV) function and regional myocardial motion patterns in the context of cardiomyopathy based on cine cardiovascular magnetic resonance (CMR). Materials and methods Following the approval of the institutional review board (IRB), standard cine images of 45 subjects, including 15 healthy volunteers, 15 patients with hypertrophic cardiomyopathy (HCM) and 15 patients with dilated cardiomyopathy (DCM) were retrospectively analyzed using HD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 18 publications
3
12
0
Order By: Relevance
“…Currently, GLS is the most widely used strain parameter for clinical echocardiographic studies Therefore, it is important to investigate if a single technique can robustly assess both longitudinal strain, where STE is an established technique, as well as circumferential strain, where tagging is an established technique. Previous results have demonstrated that GLS by DRA analysis showed a significant correlation with STE ( r = 0.47; P = 0.006) . Our results were consistent with these findings.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Currently, GLS is the most widely used strain parameter for clinical echocardiographic studies Therefore, it is important to investigate if a single technique can robustly assess both longitudinal strain, where STE is an established technique, as well as circumferential strain, where tagging is an established technique. Previous results have demonstrated that GLS by DRA analysis showed a significant correlation with STE ( r = 0.47; P = 0.006) . Our results were consistent with these findings.…”
Section: Discussionsupporting
confidence: 93%
“…The robust segmentation approach is likely one of the major reasons that contribute to the outstanding reproducibility without operator interaction. A previous study demonstrated that the reproducibility of global longitudinal, circumferential, and radial strains derived from DRA was superior to FT . Our study further confirmed this finding.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Recently, quantitative biomechanical indices acquired using magnetic resonance imaging (MRI), such as strain, strain rate, displacement and velocity, have been adopted to comprehensively describe abnormal myocardial motion patterns [ 7 ]. Compared with global indices, regional myocardial motion indices seem to be more appropriate candidates for describing subtle cardiac changes affiliated with subclinical CVDs.…”
Section: Introductionmentioning
confidence: 99%
“…Based on deformable imaging registration (DIR), heart deformation analysis (HDA) is a recently developed myocardial motion tracking technique that is able to calculate regional and global myocardial displacement, velocity, strain and strain rate on existing cine images without extra MRI scans (810). Using HDA, we measured displacement, velocity strain and strain rate on a per-segment basis (mapped on a standard 16-segment AHA LV model) at 21 healthy volunteers, and investigated the regional distributions of magnitudes for each myocardial index on the LV.…”
Section: Introductionmentioning
confidence: 99%